Identification of a Novel VPS13B Mutation in a Chinese Patient with Cohen Syndrome by Whole-Exome Sequencing - Hu X; Huang T; Liu Y; Zhang L; Zhu L; Peng X; Zhang S (Dove Medical Press, 2021)
Xiaoyun Hu, Tao Huang, Yun Liu, Lina Zhang, Li Zhu, Xiaohong Peng, Sufang Zhang Department of Pediatrics, The First Affiliated Hospital of Nanchang University, Nanchang, People's Republic of ChinaCorrespondence: Tao Huang Tel +86 13970012590Email huangtao99@email.cnObjective: The present study aims to investigate the clinical features and diagnostic characteristics of children with Cohen syndrome caused by the vacuolar protein sorting 13 homolog B (VPS13B) gene mutation and to review the relevant literature to provide a reference for genetic counseling and the diagnosis of Cohen syndrome.Methods: The clinical data and molecular genetic test results of a child with Cohen syndrome were retrospectively analyzed and a review of the relevant literature was conducted.Results: A two-year-and-four-month-old boy was referred to the hospital for recurrent fever and shortness of breath. On physical examination, the boy was found to have growth retardation, thick bushy hair, microcephaly, hypertelorism, down-slanting palpebral fissures, and hypotonia. Genetic testing was performed, and the results suggested the presence of exon 20- 32 heterozygous deletion and c.8275 delC (p.R2759 fs*18) heterozygous variant on the VPS13B gene from phenotypically normal parents. These two mutation loci have not been reported in the literature, and they were predicted by relevant software to be pathogenic variants.Conclusion: We identified two novel variants in the VPS13B gene (exon 20- 32 heterozygous deletion and c.8275 delC heterozygous variant) in a boy with Cohen syndrome, thus extending the spectrum of VPS13B gene variants in patients with Cohen syndrome.Keywords: Cohen syndrome, VPS13B gene, heterozygous mutation, heterozygous deletion